Community integration questionnaire: Outcomes of people with traumatic brain injury and high support needs compared with multiple matched controls. (23rd August 2016) - Migliorini, Christine; Enticott, Joanne; Callaway, Libby; Moore, Sophie; Willer, Barry
Abstract: Objectives : To determine level of community integration in adults with traumatic brain injury and high support needs (TBI-HSN) compared with multiple matched controls. Setting : Community setting, Victoria, Australia. Participants : Adults with TBI-HSN living in the community ( n = 61). Australian normative data ( n = 1973) was used for matching purposes (1:4). Design : Matched analysis from people with and without TBI. Matching aimed to reduce variability expected from age, gender, metropolitan/rural residence and co-resident status. Main measures : Community Integration Questionnaire (CIQ): total and sub-scales of Home Integration, Social Integration and Productivity. Results : Matched analysis showed large effects favouring the general population, e.g. CIQ total scores were significantly different, F (1, 304) = 5.8, p < 0.0001. Conditional relative risk showed community-dwelling participants with TBI were 540-times more likely to report a poor CIQ total score compared to the general population. Conclusion : Normative CIQ data has enabled meaningful comparisons of the community integration of adults with chronic TBI to the general population in Australia. Evidence makes clear with numeric precision that individuals with TBI and high support needs are much less integrated than their non-TBI counterparts despite living in the community for many years.